COVID-19 vaccine hesitancy among pregnant women in an antenatal clinic in Durban, South Africa - Sahra Ashkir; Tashlen Abel; Olive P. Khaliq; Jagidesa Moodley (Southern African Journal of Infectious Diseases, 2023)
Background: Mass administration of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the most efficient intervention against the coronavirus disease 2019 (COVID-19) pandemic. Recently, vaccinations were shown to be safe and effective during pregnancy. However, vaccination rates are low in low- and middle-income countries, and vaccine hesitancy is a major limiting factor.